2004
DOI: 10.1103/physreve.69.031704
|View full text |Cite
|
Sign up to set email alerts
|

Surface-assisted photoalignment in dye-doped liquid-crystal films

Abstract: This study examines the surface-assisted photoalignment effect of dye-doped liquid-crystal films having a homogeneous alignment. Observations made using a polarizing optical microscope, a scanning electronic microscope, and an atomic force microscope confirm that the morphology of laser-induced surface-adsorbed dyes at the command surface strongly affects the orientation of liquid crystals (LC's) in a manner that depends significantly on the intensity and duration of the pumping. In weak-intensity regime, a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 12 publications
0
64
0
Order By: Relevance
“…This result elucidates further the physics of the DDLCs since previous works have found that only the adsorption of dyes is responsible for the surface anchoring energy during illumination. [5][6][7][8] For the DDLC cell under sufficient illumination, the surface anchoring energy that is provided by the adsorption of dyes is around double that provided by the preexisting-dye-induced torque. This result indicates that the adsorption of dyes dominates the reorientation of the polar director after illumination.…”
Section: B Calculation and Discussion Of Polar Anchoring Energy Of Dmentioning
confidence: 98%
See 2 more Smart Citations
“…This result elucidates further the physics of the DDLCs since previous works have found that only the adsorption of dyes is responsible for the surface anchoring energy during illumination. [5][6][7][8] For the DDLC cell under sufficient illumination, the surface anchoring energy that is provided by the adsorption of dyes is around double that provided by the preexisting-dye-induced torque. This result indicates that the adsorption of dyes dominates the reorientation of the polar director after illumination.…”
Section: B Calculation and Discussion Of Polar Anchoring Energy Of Dmentioning
confidence: 98%
“…[1][2][3][4] The director reorientation becomes permanent if the excited dye molecules are adsorbed on the boundary surface of the DDLC cell, leading to the alignment of the LC molecules and the appearance of anchoring energy. [2][3][4][5][6] The anchoring energies of the DDLC cells are obtained by measuring using a polarized optical microscope, 5 the pumpprobe twist nematic method 6,7 and measurement of Freedericksz transition. 8 Most studies of DDLC cells have focused on the azimuthal component of the anchoring energy; [5][6][7] few have considered the polar component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies demonstrated that in LC that is doped with MR, lightinduced desorption from the spontaneously adsorbed MR layer results in the alignment of the LC perpendicular to the polarization upon exposure to light of weak intensity. Lee et al [42] suggested that the surface morphology of the adsorbed substrate depends considerably on not only the intensity but also the duration of the pumping. In the weak-intensity regime, the homogeneous and fine layer of adsorbed dyes and the layer with microgrooves dominate in the early and late stages, respectively, tending to cause the LCs to reorient perpendicular and parallel to the direction of polarization of the pump beam.…”
Section: Bulk-mediated Photo-isomerization and Adsorption Effectsmentioning
confidence: 99%
“…SEM and AFM were used to identify smooth layers of adsorbed molecules on the surfaces following exposures that caused the reorientation of the directors perpendicular to the direction of polarization and layers with well-oriented ripples upon exposures that caused alignment toward the direction of polarization [42,48]. The adsorbed layer consists of MR molecules with their long axes perpendicular to the ripples.…”
Section: Bulk-mediated Photo-isomerization and Adsorption Effectsmentioning
confidence: 99%